Land Dispute Conflict Reviewed from the Perspective of Agrarian Politics (A Study in Penandingan Village, Rantau Bayur District, Banyuasin Regency) - Nadila; Kun Budianto; Reni Apriani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study discusses the land dispute conflict in Penandingan Village, Rantau Bayur District, Banyuasin Regency, from the perspective of agrarian politics. The conflict arose due to the construction of the Extra High Voltage Air Transmission (SUTET) project by PT PLN (Persero), which created tensions between the local community and the company regarding land ownership, clarity of compensation, and overlapping land certificates. This research employs a qualitative method with a descriptive-analytical approach to explore the dynamics of agrarian politics and the impacts of the conflict. The findings reveal that this conflict reflects the inequality of land ownership, the weakness of legal protection for local communities, and the limited involvement of residents in development decision-making processes. Although conflict resolution efforts have been carried out through mediation, they have not addressed the root causes, namely fair land redistribution and formal legal recognition of land managed by communities for generations. The agrarian conflict in Penandingan Village demonstrates the weak implementation of agrarian reform and the lack of state support for rural communities, indicating the urgent need for fair, transparent, and pro-people agrarian policies to prevent similar conflicts in the future.